Uji Organoleptik Tepung Kacang Hijau Terhadap Daya Terima Konsumen Pada Kue Kering Choco Chips - Tia Listiaty,; Agung Setiawan, (Manajemen Kreatif Jurnal, 2024)
The aim of the research is to determine and analyze the substitution of green bean flour in making choco chip cookies, using experimental methods and organoleptic tests. The samples in this study were dry cakes with 50%, 75% and 100% substitution of green bean flour which were then tested on 30 panelists who assessed aspects of color, taste, aroma and texture. This research was conducted in the Pastry laboratory of the Prima International Tourism Polytechnic, Jalan Perjuangan No. 18, Kesambi District, Cirebon City. The time for carrying out this research starts from March 2024 to May 2024 using experimental methods and organoleptic tests. The consumer acceptability test was carried out on 30 panelists. Based on the results of research based on organoleptic tests, namely in terms of color, taste, aroma and taste. For the fourth aspect, the best quality was obtained by substituting 75% for green bean flour. The level of public liking for chocochips cookies substituted for green beans was obtained by substituting green beans at 75%, because the color, taste, aroma and texture produced were close to dry cookies in general.